18 kDa translocator protein positron emission tomography facilitates early and robust tumor detection in the immunocompetent SB28 glioblastoma mouse model - Bartos, Laura M.; Kirchleitner, Sabrina V.; Blobner, Jens; Wind, Karin; Kunze, Lea H.; Holzgreve, Adrien; Gold, Lukas; Zatcepin, Artem; Kolabas, Zeynep Ilgin; Ulukaya, Selin; Weidner, Lorraine; Quach, Stefanie; et al. (Frontiers in Medicine, 2022)
Introduction: The 18 kDa translocator protein (TSPO) receives growing interest as a biomarker in glioblastoma. Mouse models can serve as an important tool for the investigation of biomarkers in glioblastoma, but several glioblastoma models indicated only low TSPO-PET signals in contrast to high TSPO-PET signals of human glioblastoma. Thus, we aimed to investigate TSPO-PET imaging in the syngeneic immunocompetent SB28 mouse model, which is thought to closely represent the tumor microenvironment of human glioblastoma. Methods: Dynamic TSPO-PET/CT imaging was performed for 60 minutes after injection of 13.6±4.2 MBq [18F]GE-180. Contrast enhanced CT (ceCT) was acquired prior to PET and served for assessment of tumor volumes and attenuation correction. SB28 and sham mice were imaged at an early (week-1; n=6 SB28, n=6 sham) and a late time-point (week-3; n=8 SB28, n=9 sham) after inoculation. Standard of truth ex vivo tumor volumes were obtained for SB28 mice at the late time-point. Tracer kinetics were analyzed for the lesion site and the carotid arteries to establish an image derived input function (IDIF). TSPO-PET and ceCT lesion volumes were compared with ex vivo volumes by calculation of root-mean-square-errors (RMSE). Volumes of distribution (VTmax/mean) in the lesion were calculated using carotid IDIF and standardized-uptake-values (SUVmax/mean) were obtained for a 0-60 minute time-frame. Results: Higher uptake rate constants (K1) were observed for week-1 SB28 tumor lesions when compared to week-3 SB28 tumor lesions. Highest agreement between TSPO-PET lesion volumes and ex vivo tumor volumes was achieved with a 50% maximum threshold (RMSE-VT: 39.7%; RMSE-SUV: 34.4%), similar to the agreement of ceCT tumor volumes (RMSE: 30.1%). Lesions of SB28 mice had higher PET signal when compared to sham mice at week-1 (VTmax 6.6±2.9 vs 3.9±0.8, p=0.035; SUVmax 2.3±0.5 vs 1.2±0.1, p<0.001) and PET signals remained at a similar level at week-3 (VTmax 5.0±1.6 vs 2.7±0.8, p=0.029; SUVmax 1.9±0.5 vs 1.2±0.2, p=0.0012). VTmax correlated with SUVmax (R²=0.532, p<0.001). Conclusions: TSPO-PET imaging of immunocompetent SB28 mice facilitates early detection of tumor signals over sham lesions. SB28 tumors mirror high TSPO-PET signals of human glioblastoma and could serve as a valuable translational model to study TSPO as an imaging biomarker.